ANALISIS PENGARUH BANK SIZE, BOPO, FDR, CAR, DAN ROA TERHADAP NON-PERFORMING FINANCING (Studi Kasus Pada Perusahaan Perbankan Syariah yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016 – 2019) - Putra, Adhyasa; Syaichu, Muhamad (Diponegoro Journal of Management, 2021)
ABSTRACT Non-Performing Financing is a situation where loan repayment agreements fail, and even tend to lead to or suffer losses. The existence of problematic financing in a high amount will cause difficulties and at the same time will reduce the soundness level of the relevant Islamic bank. The aims of this study is to examine and analyze the effect of bank size, BOPO, FDR, CAR, and ROA on Non-Performing Financing (NPF) of Islamic banks in Indonesia. The population used as the sample in this study are Islamic commercial banks whose financial reports have been published to Bank Indonesia in the period 2016 to 2019. Sampling uses purposive sampling or purposive sampling according to criteria for specific purposes. The data of this research uses secondary data from the websites of each bank and Bank Indonesia. The data analysis method used is multiple linear regression analysis. The results of this study indicate that bank size and CAR have a positive and insignificant effect on Non-Performing Financing (NPF). BOPO and ROA have a significant positive effect on Non-Performing Financing (NPF). Meanwhile, FDR has a significant negative effect on NonPerforming Financing (NPF).